Heterogeneous Hollow Multi‐Shelled Structures with Amorphous‐Crystalline Outer‐Shells for Sequential Photoreduction of CO2. Issue 49 (4th November 2022) - Wei, Yanze; You, Feifei; Zhao, Decai; Wan, Jiawei; Gu, Lin; Wang, Dan
Abstract: Constructing delicate nano‐/microreactors with tandem active sites in hierarchical architectures is a promising strategy for designing photocatalysts to realize the challenging but attractive CO2 reduction. Herein, hollow multi‐shelled structure (HoMS) based microreactors with spatial ordered hetero‐shells are fabricated, which achieve two‐step CO2 ‐to‐CH4 photoreduction. The multiple inner CeO2 shells increase the number of active catalytic sites to ensure efficient first‐step reaction for generating CO, along with enriching the local CO concentration. The second‐step CO‐to‐CH4 reaction is consequently induced by amorphous TiO2 (A‐TiO2 ) composites on the adjacent outer‐most shell, thus realizing the CO2 ‐to‐CH4 conversion capability using one CeO2 @CeO2 /A‐TiO2 HoMS. In‐depth explorations in the microreactors provide compositional, structural, and interfacial guidance for engineering HoMS‐based microreactors with temporally–spatially ordered shells toward efficient tandem catalysis. Abstract : In this work, photocatalytic CO2 ‐CO‐CH4 conversion is realized by hollow multi‐shelled structure (HoMS) based microreactors with hetero‐shells. The enriched local CO concentration in inner shells and continuous protonation of CO on the outer‐most shell enable the two‐step tandem CO2 ‐to‐CH4 conversion, which provide compositional, structural, and interfacial guidance for engineering hierarchical microreactors toward efficient tandem catalysis.